2002
DOI: 10.2337/diabetes.51.10.2911
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Is Not Necessary for Adequate Hormonal Counterregulation of Insulin-Induced Hypoglycemia

Abstract: Ghrelin is a novel enteric hormone that stimulates growth hormone (GH), ACTH, and epinephrine; augments plasma glucose; and increases food intake by inducing the feeling of hunger. These characteristics make ghrelin a potential counterregulatory hormone. At present, it is not known whether ghrelin increases in response to insulin-induced hypoglycemia. To answer this question, we compared plasma ghrelin concentrations after a short-term insulin infusion that was allowed or not (euglycemic clamp) to cause hypogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
93
2
8

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 28 publications
19
93
2
8
Order By: Relevance
“…It has also been shown that the postprandial decline in ghrelin levels is less pronounced in obese compared to lean subjects (le Roux et al, 2005), and insulin resistance measured by euglycaemic hyperinsulinemic clamp was described inversely related to the insulininduced decrease in total serum ghrelin levels (Lucidi et al, 2002). This might explain the reduced decrease in postprandial total ghrelin response in insulin-resistant subjects as observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…It has also been shown that the postprandial decline in ghrelin levels is less pronounced in obese compared to lean subjects (le Roux et al, 2005), and insulin resistance measured by euglycaemic hyperinsulinemic clamp was described inversely related to the insulininduced decrease in total serum ghrelin levels (Lucidi et al, 2002). This might explain the reduced decrease in postprandial total ghrelin response in insulin-resistant subjects as observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…In most but not all (22) cross-sectional studies, reduced ghrelin levels are found in subjects with impaired insulin sensitivity (14-17), but insulin resistance has also been associated with a blunted postprandial suppression of ghrelin (3,21). The specific role of insulin appears more evident since most studies including the present show that insulin administration lowers ghrelin levels irrespective of ambient glycemia.…”
Section: Discussionmentioning
confidence: 76%
“…24,32 Several studies have shown a close relationship between insulin and ghrelin secretion. Insulin infusion decreased ghrelin concentrations in healthy subjects [33][34][35] and basal insulin levels have been found to correlate negatively with ghrelin levels. 7,36 In our previous study, we demonstrated a close inverse association between the circulating concentrations of insulin and ghrelin both preoperatively and 6 and 12 months after gastric bypass.…”
Section: Discussionmentioning
confidence: 93%